Validity of the Implementing Regulations of Law Number 7 of 2004 concerning Water Resources Post-Constitutional Court Decision Number 85 / Puu-Xi / 2013 - Muhammad Fauzul Adzim (Fakultas Hukum Universitas Lampung, 2020)
The power of law of statutory norms under the law after the reference regulation can be canceled by the Constitutional Court. The validity of the legal strength of implementing regulations from Law Number 7 of 2004 concerning Water Resources can be determined through a higher legal norm above it because a higher norm will lead to a basic norm which becomes the source of the legal norms under it. Likewise with implementing regulations of a law, the validity of which is determined by the legal norms above it as a whole or per article because the legal norms above are sourced and lowered as sources. In accordance with the theory put forward by Adolf Merkel in the theory of legal ranking, which states that a legal norm has two faces, das Doppelte Rechtsanlitz. Adolf revealed that a norm is upward as a source and basis for legal norms underneath. Thus, the validity of the implementing regulations of Law Number 7 of 2004 concerning Water Resources will lose its validity when the source norms have been canceled by the Constitutional Court so that amendments to Law Number 12 of 2011 concerning the Formation of Laws and Regulations by the DPR and President.